PERBAIKAN LINGKAR PERUT, TEKANAN DARAH, DAN BODY MASS INDEX WANITA SINDROM METABOLIK MENGGUNAKAN YOGURT SUSU KECAMBAH KACANG MERAH - Hery Winarsi; Aisyah Tri Septiana; Avia Roselina (Jurnal Gizi dan Pangan Soedirman, 2020)
This study aims to determine the effect of red kidney bean sprout milk yogurt (Rides-Yo) on abdominal circumference, blood pressure, and body mass index of metabolic syndrome women. Red kidney bean sprouts milk added with 10% sucrose and 10% skim milk pasteurized at 70 ° C for 10 minutes, then cooled to 45oC. Inoculated with lactic acid bacteria 2% of the total volume of red bean milk, incubated at 27-35oC for 24 hours. As many as 30 women, 40-65 years aged, central obesity, hypertension, and hyperlipidemia, live in the Baturraden subdistrict, Banyumas Regency, and are willing to sign informed consent. Subjects were randomly divided into 3 groups; the first group was given Rides-Yo; the second group was given a placebo; and group 3 took medicine from a doctor. A total of 200 mL/day of Rides-Yo or placebo was given to the subjects for 2 months. Before and after the intervention, subjects were measured for abdominal circumference, blood pressure, weight and height. There was a decrease in abdominal circumference (P=0,018), systole and diastolic blood pressure (P <0.038 and P=0,032), and BMI (P=0,039) in the group receiving Rides-Yo, compared to placebo and control groups. Thus, Rides-Yo is able to improve the health status of women with metabolic syndrome.